2016
DOI: 10.22246/jikm.2016.37.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Medicine on Patients with Idiopathic Parkinson’s Disease: A Retrospective Study

Abstract: The purpose of this study was to investigate the effects of Korean medicine on patients with idiopathic Parkinson's disease. Methods: The charts of 47 patients diagnosed with idiopathic Parkinson's disease in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In Hartmann's study [43], they compared Bee-venom pharmacopuncture with a group injected with saline solution, and concluded that there were no significant differences between the 2 groups. However, there are many differences among the study, frequency and method of treatment of Yang et al [40]. In this study, an intracutaneous injection of Beevenom pharmacopuncture was performed once a month.…”
Section: Acupoints Numbermentioning
confidence: 94%
See 1 more Smart Citation
“…In Hartmann's study [43], they compared Bee-venom pharmacopuncture with a group injected with saline solution, and concluded that there were no significant differences between the 2 groups. However, there are many differences among the study, frequency and method of treatment of Yang et al [40]. In this study, an intracutaneous injection of Beevenom pharmacopuncture was performed once a month.…”
Section: Acupoints Numbermentioning
confidence: 94%
“…In 2016, Lee et al [39] injected 5% Bee-venom pharmacopuncture into Hoku (LI4), Quchi (LI11), Yanglingquan (GB34), Taichong (LR3), and Zusanli (ST36) in early Parkinson's disease patients. Yang et al [40] placed the Beevenom pharmacopuncture diluted with 1:20,000 distilled water in both Taichong (LR3), Yanglingquan (GB34), Zusanli (ST36), Quchi (LI11), and Fengchi (GB20) for 47 patients in a retrospective study. Yang et al [41] reported in his 2017 paper that the same Beevenom pharmacopuncture had been used for the same acupoints, which was the same method used in the studies by Cho et al [36] and Doo et al [42].…”
Section: Acupoints Numbermentioning
confidence: 99%
“…Indeed, previous studies have shown that herbal formulas, acupuncture and tai chi might be safe and beneficial to PD patients (Bega and Zadikoff, 2014; Cwiekala-Lewis et al, 2017; Lee and Lim, 2017; Noh et al, 2017; Shan et al, 2018). In addition, there have been studies to find out the benefit of using biomedicine and KM concurrently in PD patients (Leem, 2016; Yang et al, 2016; Jang et al, 2018; Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…List of Diseases that Reported Case Reports Related to Ukgan-san in Korean AcademicField[17][18][19][20][21][22][23][24][25][26][27][28] …”
mentioning
confidence: 99%